1992
DOI: 10.2307/144184
|View full text |Cite
|
Sign up to set email alerts
|

Linked Migration Systems: Immigration and Internal Labor Flows in the United States

Abstract: The relationship between immigration to and labor movements within the United States is examined using a model that links migration, occupations, production and institutional relations in the economy, and economic restructuring. The authors conclude that "native blue-collar workers have been spatially displaced by recent immigration and that the process of capital accumulation, as manifested in economic restructuring, is the driving force behind the mobility system, affecting both immigration patterns and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 36 publications
5
46
0
1
Order By: Relevance
“…Portions of census-derived population are released to the seed cities over the simulation run at rates commensurate with historical records. This represents in-migration to the system [132]. Endogenous change is also possible, as already explained, and this population has the ability to mobilize within the simulated city-system.…”
Section: Simulating Sprawl In the American Midwestmentioning
confidence: 81%
“…Portions of census-derived population are released to the seed cities over the simulation run at rates commensurate with historical records. This represents in-migration to the system [132]. Endogenous change is also possible, as already explained, and this population has the ability to mobilize within the simulated city-system.…”
Section: Simulating Sprawl In the American Midwestmentioning
confidence: 81%
“…Complementary migration streams are also a possibility with highly skilled professional migrants moving to the same locations as relatively unskilled immigrants; the latter providing service labor for the former (Nelson et al 2009;Nelson and Nelson 2011). The evidence on these linkages is disputed with some studies finding more support (Borjas 2001) than others (Walker et al 1992;.…”
Section: Linking Internal and International Migrationmentioning
confidence: 99%
“…Indeed, research on contemporary labor mobility has found that native-born workers are less likely to migrate to urban areas where immigrants are concentrated. 55 Furthermore, foreign-born workers are less likely to move out of states where they are concentrated than are native born. 56 Both features cause an accentuation of the impact of immigration in those urban labor markets where immigrants are concentrated.…”
Section: The "Fourth Wave" Of Immigration: Its Relevance To Black Amementioning
confidence: 99%